Economics in Sweden - Engwall, Lars (Taylor & Francis, 1992)
Economics in Sweden contains the results of one of the most comprehensive attempts to evaluate research in economics ever undertaken. A team of Swedish and international researchers, including Avinash K. Dixit, Seppo Honkapohja and Robert M. Slow, examined the structure of economics in Sweden and its results. They identified postgraduate education as a key area, and their findings will be of particular relevence at a time when many countries are restructuring their graduate education programme.